Evaluation of H2O2, H2, and bubble temperature in the sonolysis of water and aqueous t-butanol solution under Ar: Effects of solution temperatures and inorganic additives of NaCl and KI - Yuki Nakata; Yoshiteru Mizukoshi; Kenji Okitsu (Ultrasonics Sonochemistry)
The yields of H2O2 and H2 formed in the sonolysis of aqueous solution under noble gas are representative indexes for understanding the chemical effects of ultrasonic cavitation bubbles. In this study, the yields of H2O2 and H2 formed under Ar were evaluated as a function of the concentration of NaCl or KI. When these yields were analyzed by using a normalization technique, it was confirmed that the yields of H2 were more clearly related to Ar solubility than those of H2O2, suggesting that H2 is a more real probe to understand the chemical effects of cavitation bubbles in water. The effects of NaCl on sonochemical formation of oxidants were also compared with those of KI. When aqueous t-butanol solution was sonicated, the yields of H2 and the maximum temperature attained in a collapsing bubble (bubble temperature) decreased with increasing solution temperature and salt concentration, suggesting that these parameters affected the quantity related to the number (and/or size) of active bubbles as well as the quality related to the bubble temperatures.